LA TRANSFORMADA DE LAPLACE EN LA SOLUCIÓN DE ECUACIONES DIFERENCIALES CON ALGORITMO DE CÁLCULO EN MATHCAD - JUAN ANTONIO MARTIN ALFONSO; CARLOS MANUEL MATA RODRÍGUEZ (Revista Ingeniería, Matemáticas y Ciencias de la Información)
In the history of Mathematics, frequently happens that certain topics (especially the numeric calculation) has perfectlydefined its theoretical solution, but the heap of operations to find a conclusive result, in multiple occasions, don’t allowto arrive to the final results.